Intrahepatic mRNA levels of SOCS1 and SOCS3 are associated with cirrhosis but do not predict virological response to therapy in chronic hepatitis C. (14th November 2012) - Pascarella, Stéphanie; Clément, Sophie; Dill, Michael T.; Conzelmann, Stéphanie; Lagging, Martin; Missale, Gabriele; Neumann, Avidan U.; Pawlotsky, Jean‐Michel; Zeuzem, Stefan; Rubbia‐Brandt, Laura; Bochud, Pierre‐Yves; Negro, Francesco
Abstract: Background: Antiviral treatment of chronic hepatitis C is not invariably successful, costly and associated with serious side‐effects, and therefore should be indicated only when the chances of benefitting patients exceed the potential risks. The suppressor of cytokine signalling (SOCS) family members have been suggested to affect the rate of virological response to therapy, but the published evidence is conflicting. Methods: We measured the intrahepatic SOCS1, SOCS3 and SOCS7 mRNA levels in 107 chronic hepatitis C patients and assessed their clinical and histological correlates with the virological response to therapy and with some factors known for affecting treatment outcome. Results: By multivariate analysis, SOCS1, SOCS3 and SOCS7 mRNA levels were not associated with rapid or sustained virological response. Similarly, no association was found between the levels of any intrahepatic SOCS mRNA and those of the homeostasis model assessment of insulin resistance. Conversely, SOCS1 (OR 2.185, 95% CI 1.223–3.906, P =0.0083) and SOCS3 (OR 40.601, 95% CI 2.357–699.25, P =0.0108) mRNA level (but not SOCS7), together with age (OR 1.156, 95% CI 1.049–1.275, P =0.0036), were independently associated with cirrhosis. Conclusions: Intrahepatic SOCS1, SOCS3 and SOCS7 mRNA levels do not predict virological response to therapy in chronic hepatitis C. The association between SOCS1, SOCS3 and cirrhosis warrants further study.